การเลือกใช้สิทธิการรักษาภายใต้ระบบประกันสุขภาพในประเทศไทย - น้ำใจดี, รัชนีบูล (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 25 No 2 (2557): Academic Services Journal, Prince of Songkla University, 2014)
งานวิจัยนี้มีวัตถุประสงค์ เพื่อศึกษาปัจจัยที่มีความสัมพันธ์กับการเลือกใช้สิทธิการรักษาและรูปแบบของระบบประกันสุขภาพที่ผู้ป่วยต้องการ เก็บรวบรวมข้อมูลจากผู้ป่วยที่ใช้บริการแผนกผู้ป่วยนอกของโรงพยาบาลรัฐ 1 แห่ง และโรงพยาบาลเอกชน 1 แห่ง จำนวน 400 คน ในเดือนมีนาคม–กรกฎาคม 2555 โดยใช้แบบสอบถามซึ่งมีค่าความเชื่อมั่นในส่วนของทัศนคติที่มีต่อบริการด้านสุขภาพ เท่ากับ 0.88 วิเคราะห์ข้อมูลโดยใช้สถิติเชิงพรรณนา หาความสัมพันธ์ของตัวแปรโดยใช้การทดสอบไคสแควร์ (Chi-square test) ผลการวิจัยพบว่า มีผู้ป่วยไม่ใช้สิทธิการรักษาพื้นฐานร้อยละ 28.3 และร้อยละ 64.8 เคยเปลี่ยนสิทธิการรักษาในรอบ 2 ปี มีปัจจัยที่มีความสัมพันธ์กับการเลือกใช้สิทธิการรักษา ดังนี้ ปัจจัยที่มีอยู่ก่อน ได้แก่ อายุ ระดับการศึกษา และทัศนคติด้านการรักษา และพบว่า ผู้ป่วยที่มีอายุมากกว่า 37 ปี ผู้ป่วยที่มีระดับการศึกษาระดับตํ่ากว่าปริญญาตรี และผู้ที่มีทัศนคติด้านการรักษาระดับปานกลางขึ้นไป จะใช้สิทธิการรักษาพื้นฐานของตนเป็นส่วนใหญ่ ปัจจัยสนับสนุน ได้แก่ รายได้และสิทธิการรักษาพื้นฐาน โดยพบว่า ผู้ป่วยที่มีรายได้น้อยกว่า 20,000 บาท ผู้ที่มีสิทธิสวัสดิการข้าราชการจะใช้สิทธิการรักษาพื้นฐานของตนเป็นส่วนใหญ่ ปัจจัยด้านความจำเป็น ได้แก่ การมีโรคประจำตัวและลักษณะของความเจ็บป่วย โดยพบว่า ผู้ป่วยที่มีโรคประจำตัวและมีลักษณะอาการของโรคเรื้อรังจะใช้สิทธิการรักษาพื้นฐานของตนเป็นส่วนใหญ่ โดยปัจจัยเหล่านี้มีความสัมพันธ์กับการเลือกใช้สิทธิการรักษาอย่างมีนัยสำคัญทางสถิติ (P<.05) ผู้ป่วยส่วนใหญ่ ร้อยละ 52.5 มีความเห็นว่า ระบบประกันสุขภาพควรมีระบบเดียวกันทั้งประเทศ ผู้ป่วยร้อยละ 55.5 มีความเห็นว่า ควรมีส่วนร่วมจ่าย ซึ่งมีความสามารถจ่ายได้เฉลี่ย 95.33 บาทต่อครั้ง ข้อเสนอแนะจากงานวิจัย คือ มีประชาชนกลุ่มหนึ่งที่มีความสามารถจ่ายค่ารักษาด้วยตนเอง ซึ่งกลุ่มนี้เป็นกลุ่มที่โรงพยาบาลเอกชนควรให้ความสนใจเป็นลำดับแรก ภาครัฐควรทำการศึกษาทัศนคติของประชาชนทั้งประเทศที่มีต่อระบบประกันสุขภาพในปัจจุบันและความสามารถในการมีส่วนร่วมจ่าย เพื่อนำไปกำหนดนโยบายสาธารณสุขที่ตอบสนองต่อความต้องการของประชาชนอย่างแท้จริง Though the Thais have benefit use at point of services designated by the state but at present, it was found that parts of them do not use the benefit when being sick. This quantitative research has the objectives to investigate factors relating the choice of benefits use at point of services and the model of the health insurance system needed by patients. Questionnaire was used in the data collection with the values of confidence regarding the attitudes towards the health service at 0.88 among the 400 outpatients in a public hospital and a private hospital during March to July 2012. The statistical applications were descriptive and Chi-square test was applied to find their relationship.  28.3% of the patient had no benefits use and 64.8% had ever change their benefits use within 2 years round. Factors having relationship with the choice of benefits  use at point of services were, age, education level, attitudes toward treatment which were the predisposing factors. It was found that patients with ages older than 37 years, patients with below bachelor degree and patents with moderate attitudes toward treatment would mostly apply for their benefits use. In the enabling factors, they were income and basic benefits use. It was found that patients earning less than 20,000 Baht and patients with official welfare would mostly apply for their basic benefits use. In the need factors, they were patients with congenital disease, and nature of illness. It was found that patients with congenital disease and chronic disease would mostly apply for their basic benefits use. These factors had relationship with the choice of benefits use at point of services by statistical significance (P<.05). 52.5% of patients commented that health insurance should, nationwide, be only one system. 55.5% of the patients commented that there should be pay-sharing for those who were affordable at 95.33 Baht by average a time.  Recommendations from the study were that there was a group of people who were affordable for the treatment. The private hospitals should pay attention to this group as priority. The public sector should investigate public attitudes,  nationwide, toward the health insurance at the moment and their affordability in order to design policy of the public health to really meet their needs.